Outcome of 49 Iraqi adult patients with Chronic Lymphocytic Leukemia treated with oral alkylating agent: - Naji, Alaadin S. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: Chronic lymphocytic leukemia (CLL) is a heterogeneous disease with an extremely variable course. Survival after diagnosis can range from months to decades and wide variability exists in the rate of disease progression and the incidence of disease-related complications among patients with CLL. Staging helps to define prognosis and to decide when to initiate therapy. Objective: To asses response to oral alkylating therapy and to evaluate the adverse events that can complicate the disease itself or the treatment, including infections, autoimmune and other complications. The survival events are also been assessed. Patients and methods: Forty nine Iraqi CLL patients, their age ranged between 40-90 years were followed with median duration of 28 months. During the follow up period of these patients, the events that complicated the disease or therapy were recorded. The primary endpoints were response rates, quality of response, Secondary endpoints of the study were overall survival , progression-free survival and event free survival. Response rates were calculated for 40 patients who were treated for at least 6 months. All patients were treated with intermittent pulse therapy of oral single alkylating agent. Results: The majority of patients recruited either had intermediate or advanced stage disease in 45(91%) patients .Autoimmune phenomena, were documented in 5(10.2%)patients. There was increased incidence of infections with either viral or bacterial pathogen, complicating the course of disease in 20 (40.8%). Remission state was mainly with partial response in 26/40(65%).In12(24.4%) patients the disease progressed and death occurred in 6(12.2% ) patients ,4(8.1% )of them were CLL(related) and 2(4.08%)of them unrelated(stroke, ischemic heart disease) to CLL with median progression free survival(PFS)and overall survival(OS) for these patients were not reached, with 2 years PFS and OS were70%. Conclusion: Although CLL is an indolent disease still the course is complicated by many events like autoimmune problem and infections whether related to CLL or to treatments. Alkylating agent were effective therapy in the treatment of CLL and the majority of patients in this study partially responded